Experimental investigation on the chimney divergence and wire mesh influences on the performance of solar chimney - Ahmed Jawad (2020)
Solar chimney power generation system is a renewable alternative option to fossil fuels to generate electric energy, but its construction and maintenance are expensive. A lot of innovative prototypes of solar chimneys were developed by researchers to reduce costs related to its size, yet no significant solution has been established. This study aims to investigate the performance of divergent solar chimney compared to cylindrical-solar chimney at different inlet heights and electric heat loads. The electric heating load is gained from the electrical coil located below the chimney to simulate the solar energy in the collector. Scaled down divergent and cylindrical solar chimney models were designed and fabricated in the lab. The working parameter of the scaled down solar chimney was measured at different electric heat loads to observe the performance variants. A wire mesh addition at the chimney exit was also tested and analysed to study the effect of cold inflow to divergent solar chimney performance. Experimental results of the divergent chimney showed improved stack effect and increases in velocity at the throat caused by the reduced area. The power potential of the chimney is also increased from 6 to 15 times compared to a cylindrical chimney. Wire mesh addition at the exit of the chimney prevents cold inflow by the formation of eddies due to flow separation and an increase in turbulence flow. As such, it causes improved flow behaviour and an increase in air velocity by 30%. This study concludes that divergent chimney has a better performance compared to a cylindrical chimney. The addition of wire mesh further increases the power potential of the divergent solar chimney. These findings show that the divergent solar chimney is a highly probable alternative design to reduce capital cost by reducing the height while having better power potential.